ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI TUKAR RUPIAH TERHADAP DOLLAR - Laurensia Tania (2023)
Indonesia is a country with a strategic location and traversed by international trade routes, but Indonesia still depends on export and import for domestic needs. The rupiah exchange rate has a big contribution to international trade activities, namely as a means of payment. In addition, the exchange rate has a function in maintaining the balance of payments, maintaining market stability in a country, as well as a tool for sterilization and expanding the money supply, which each of these functions has a stake in growth and maintaining the stability of the Indonesian economy. This research is a quantitative study which aims to determine the effect of foreign direct investment, money supply, trade openness, and world oil prices on the rupiah exchange rate. Data collection techniques used are documentation and literature. The population used in this study is data on the rupiah exchange rate, foreign direct investment, money supply, trade openness, and world oil prices in the Indonesian region with the sample being the same variable as the annual time span from the 1991-2021 period. This research uses non-probability sampling with saturated sampling technique. The hypothesis was tested using Multiple Linear Regression Analysis using the E-views 10 program and a significance level of 5% (0.05). The results of the study partially show that foreign direct investment, the money supply, trade openness, and world oil prices have an influence on the rupiah exchange rate.